Pancreatic Mucinous Cystic Neoplasm in a Male Patient - Casadei, Riccardo; Pezzilli, Raffaele; Calculli, Lucia; Santini, Donatella; Taffurelli, Giovanni; Ricci, Claudio; D’Ambra, Marielda; Minni, Francesco (JOP. Journal of the Pancreas, 2012)
Context Mucinous cystic neoplasm (MCN) of the pancreas usually affects female patients and is characterized by an ovarian-type stroma. From literature review, only 9 cases of MCNs have been reported in male patients. Case report We describe the 10th case of a MCN in a 65-year-old male patient who underwent a distal pancreatectomy with spleen resection and standard lymphadenectomy. Conclusions MCN may rarely regard male patients, probably for embryological abnormalities. Image: MRCP showing a 49 mm fluid mass in the body-tail of the pancreas.